2017
DOI: 10.1152/jn.00636.2016
|View full text |Cite
|
Sign up to set email alerts
|

The absence or temporal offset of visual feedback does not influence adaptation to novel movement dynamics

Abstract: Delays in transmitting and processing sensory information require correctly associating delayed feedback to issued motor commands for accurate error compensation. The flexibility of this alignment between motor signals and feedback has been demonstrated for movement recalibration to visual manipulations, but the alignment dependence for adapting movement dynamics is largely unknown. Here we examined the effect of visual feedback manipulations on force-field adaptation. Three subject groups used a manipulandum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…Another consideration is that in our experiments, viscosity was fixed throughout each trial; in followup experiments, it would be interesting to calibrate the nature and degree of movement perturbations to observe the resulting effects on timing. For example, experimenters could introduce dynamic perturbations or alter visual feedback much like in motor adaptation experiments ( Shadmehr and Mussa-Ivaldi, 1994 ; Krakauer et al, 2000 ; Alhussein et al, 2019 ; McKenna et al, 2017 ; Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is that in our experiments, viscosity was fixed throughout each trial; in followup experiments, it would be interesting to calibrate the nature and degree of movement perturbations to observe the resulting effects on timing. For example, experimenters could introduce dynamic perturbations or alter visual feedback much like in motor adaptation experiments ( Shadmehr and Mussa-Ivaldi, 1994 ; Krakauer et al, 2000 ; Alhussein et al, 2019 ; McKenna et al, 2017 ; Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each individual trial was then centered, based on the peak velocity, with a temporal window of 1,200 ms (Ϯ600 ms); this window ensured the complete movement was captured. The linear regression coefficient of the force applied laterally by subjects to the ideal force was determined to quantify an adaptation coefficient value on any given trial (Hosseini et al 2017;Joiner and Smith 2008;Joiner et al 2011Joiner et al , 2013Joiner et al , 2017McKenna et al 2017;Sing et al 2009;Wagner and Smith 2008). To counter any initial biases (measured from preadaptation ECs placed throughout baseline blocks), mean baseline force profiles were subtracted from subsequent force profiles recorded on an individual basis (Gonzalez Castro et al 2014;Hosseini et al 2017;Joiner and Smith 2008;Joiner et al 2011Joiner et al , 2013Joiner et al , 2017McKenna et al 2017;Sing et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, can experience-based plasticity in the temporal aspect of sensory predictions negate the otherwise detrimental effects of feedback delays when learning to adapt to a different sensorimotor perturbation? Initially, this appeared to be not the case as Tanaka et al (2011) found no improvement in prism glass 1 It has been shown that visual feedback delays of 75 or 150 ms during reaching movements had no statistically significant effect on adaptation to a force field (i.e., a somatosensory perturbation), but in that case even the complete absence of visual feedback did not significantly disrupt learning (McKenna et al, 2017). adaptation with 136 ms visual feedback delay (100 ms added delay, 36 ms equipment delay) if subjects had also experienced the same delay before vision was shifted.…”
Section: Introductionmentioning
confidence: 99%